IDH-mutant gliomas in children and adolescents - from biology to clinical trials - Evans, Louise; Trinder, Sarah; Dodgshun, Andrew; Eisenstat, David D.; Whittle, James R.; Hansford, Jordan R.; Valvi, Santosh (Frontiers in Oncology, 2025)
Gliomas account for nearly 30% of all primary central nervous system (CNS) tumors in children and adolescents and young adults (AYA), contributing to significant morbidity and mortality. The updated molecular classification of gliomas defines molecularly diverse subtypes with a spectrum of tumors associated with age-distinct incidence. In adults, gliomas are characterized by the presence or absence of mutations in isocitrate dehydrogenase (IDH), with mutated IDH (mIDH) gliomas providing favorable outcomes and avenues for targeted therapy with the emergence of mIDH inhibitors. Despite their rarity, IDH mutations have been reported in 5-15% of pediatric glioma cases. Those with primary mismatch-repair deficient mIDH astrocytomas (PMMRDIA) have a particularly poor prognosis. Here, we describe the biology of mIDH gliomas and review the literature regarding the emergence of mIDH inhibitors, including clinical trials in adults. Given the paucity of clinical trial data from pediatric patients with mIDH glioma, we propose guidelines for the inclusion of pediatric and AYA patients with gliomas onto prospective trials and expanded access programs as well as the potential of combined mIDH inhibition and immunotherapy in the treatment of patients with PMMRDIA at high risk of progression.